Effect of egg consumption on early childhood development: evidence from Un Oeuf study - Helen Ernyey; Chhavi Tiwari; Heather Stark; Emma Hunniford; Aissata Wereme N’Diaye; Yacouba Zare; Anteneh Omer; Sarah Lindley McKune (Public Health Nutrition)
Abstract